1984
DOI: 10.1128/mcb.4.10.2041
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Neurospora crassa with recombinant plasmids containing the cloned glutamate dehydrogenase (am) gene: evidence for autonomous replication of the transforming plasmid.

Abstract: We have characterized Neurospora crassa transformants obtained with plasmid pJR2, which consists of the Neurospora glutamate dehydrogenase (am) gene cloned in pUC8 and an am'32 host strain which contains a deletion encompassing the cloned fragment. Every one of 33 transformants tested showed extreme meiotic instability: less than 1 or 2% am+ progeny were obtained in initial or successive backcrosses between am' transformants and am'32 or in intercrosses between am+ progeny. Furthermore, am+ progeny from backcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Recently, a report has been published that states that plasmid rearrangements also occur in S. cerevisiae (10). But it seems that rearrangements (tandem duplication, deletion) are more frequent in S. pombe, and very similar observations were made in Neurospora crassa (15). We expect that introduction of additional sequences into the vectors (e.g., for cloning experiments) may alter plasmid behavior in S.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, a report has been published that states that plasmid rearrangements also occur in S. cerevisiae (10). But it seems that rearrangements (tandem duplication, deletion) are more frequent in S. pombe, and very similar observations were made in Neurospora crassa (15). We expect that introduction of additional sequences into the vectors (e.g., for cloning experiments) may alter plasmid behavior in S.…”
Section: Discussionmentioning
confidence: 66%
“…On the basis of these observations, Selker and colleagues (1) suggested that RIP may be a general response ofthe organism to duplications of chromosomal segments. This would explain observations of non-Mendelian inheritance of transforming DNA in Neurospora (6,7). In addition, it would explain the classical observation that segmental aneuploids are infertile ("barren") in Neurospora (see ref.…”
mentioning
confidence: 99%
“…One of these sequences greatly enhances the transformation efficiency of A. nidulans, but the vector containing this ansl sequence remains integrative. In Neurospora crassa, a recombinant pUC8 plasmid carrying the am gene has been reported to be able to replicate autonomously (8). However, the transforming vector is rearranged and is present as high-molecular-weight concatemers; furthermore, some plasmid sequences are integrated into the chromosomal DNA.…”
mentioning
confidence: 99%